Global attractor for non-autonomous wave equation without uniqueness of solution - Iovane, G.; Kapustyan, O.V. (Системні дослідження та інформаційні технології, 2006)
In the paper the non-autonomous wave equation with non-smooth right-hand side is considered. It is proved that all its weak solutions generate multi-valued non autonomous dynamical system, which has invariant global attractor in the phase space.